Autophagy Induced by Proteasomal DUB Inhibitor NiPT Restricts NiPT-Mediated Cancer Cell Death - Chen, Jinghong; Chen, Xin; Xu, Dacai; Yang, Li; Yang, Zhenjun; Yang, Qianqian; Yan, Ding; Zhang, Peiquan; Feng, Du; Liu, Jinbao (Frontiers in Oncology, 2020)
Ubiquitin-proteasome system (UPS) and autophagy-lysosome pathway (ALP) are two major systems for protein quality control (PQC) in eukaryotic cells. Inter-connectivity between these two pathways has been suggested but the molecular detail of how they impact each other remains elusive. Proteasomal deubiquitinase (DUB) is an important constituent in the UPS and has proved to be a novel anticancer target. We have previously found that a novel DUB inhibitor, nickel complex NiPT, induces apoptosis in both cultured tumor cell lines and cancer cells from acute myeloid leukemia human patients. In this study, we found that NiPT triggered autophagy both in vitro and in vivo. Mechanistically, NiPT targets two DUBs, USP14 and UCHL5 and increased the level of poly-ubiquitination of autophagy receptor P62. Deletion of the UBA domain of P62 that is required for poly-ubiquitin binding prevented NiPT-induced autophagy. NiPT-induced autophagy is through either concomitant activation of AMP-activated Protein Kinase (AMPK) and inhibition of Mechanistic Target of Rapamycin (mTOR) signaling, or eliciting ER-stress by activating (Activating transcription factor 4) ATF4 and CHOP (C/EBP-homologous protein). Moreover, NiPT could induce more lung cancer cells undergoing apoptosis if synergistically using autophagy inhibitors, suggesting that NiPT-induced autophagy protects cancer cell from death. Collectively, our findings demonstrate that autophagy inhibition enhances the anticancer effects of proteasomal DUB inhibitor and might be an effective treatment strategy for lung cancer.